North-northwest shortening across Laramide structures in the southeastern Uinta Mountains, Colorado and Utah - Gregson, Joe Denny, author; Erslev, Eric A., advisor; Paulson, Merlyn J., committee member; Ethridge, Frank G., committee member; Sutton, Sally J., committee member (Colorado State University. Libraries, 1994)
The Rocky Mountain foreland consists of a series of anastomosing structural arches that vary greatly in trend. Several previous studies of Laramide faulting document predominantly northeast-southwest shortening that is independent of arch orientation. Laramide faults and folds in the southeastern Uinta arch, however, suggest a north-northwest shortening direction. Laramide structures in the Dinosaur National Monument area were examined to investigate the possibility of north-northwest shortening. Eigenvector, M-plane, conjugate fracture, octahedra, and direct stress inversion analyses of 1206 slickensided minor faults give slip and σ1, trends averaging N22°W. Although the slip and σ1 trends are nearly perpendicular to individual structural trends, suggesting local control of stress and strain fields by the structures, a consistent component of northwesterly slip indicates north-northwest compression. To test this unusual Laramide σ1 direction, a 3-D restoration of the compressional Yampa graben area was constructed. The optimum restoration gave similar slip trends (N48°W N25°W) with clockwise rotations of 1° to 4° for the deformed blocks. The north-northwest shortening and σ1 trends in the Dinosaur area are highly oblique to the northeasterly trends elsewhere in the foreland. Hypotheses explaining the σ1 and shortening trends in the study area include: 1) north-south contraction from bending in the thrust slab over a south-dipping listric ramp during northeasterly thrusting of the range, 2) right lateral shear due to the complex transition in structural vergence between the northeast-directed Uinta arch and southwest-directed White River uplift, and or 3) eastward translation of the Uinta structural block due to impingement of the Sevier thrusts from the west. A combination of hypotheses 1 and 2 appear to best explain the observations and are favored as more proximal deformation mechanisms. The diverse structural trends in the study area probably resulted from both local and regional Laramide stresses, neither of which can be ignored in kinematic studies of foreland deformation.
Keywords: Geology, Structural -- Rocky Mountains Region; Geology -- Uinta Mountains (Utah and Wyo.)